Recrystallization nucleation in stable aluminium-base single crystals: Crystallography and mechanisms. (15th February 2017) - Miszczyk, M.M.; Paul, H.; Driver, J.H.; Drzymała, P.
Abstract: The predominant crystallographic relations between nuclei and simple deformation structures have been characterized in Al and Al-1%wt.Mn alloy single crystals of stable Goss{011}〈001〉 and brass{110}〈112〉 orientations. Samples were deformed in a channel-die to develop a homogeneous structure comprising two sets of symmetrical microbands and then lightly annealed to 10%–20% recrystallization. SEM/EBSD measurements revealed that the misorientation angles across the recrystallization interfaces are grouped in the range 25–55° (with a maximum at 35–45°) around axes located near, but rarely at, the normals of {111} planes. These misorientations are much higher than those of the as-deformed state. There is also a strong relation between as-deformed orientations and the limited number of recrystallized grain orientations, some of which exhibited growth anisotropy along {111} planes. The results are discussed in terms the creation of twist (low mobility) or tilt (high mobility) grain boundaries of high misorientation by thermally activated, co-ordinated movement of dislocations during recovery. The grain boundaries along which the privileged growth occurs are classified as twist-type since the normal to the boundary plane coincides with the misorientation rotation axis. Graphical abstract: The crystal lattice rotation of elongated grains takes place around axes near the 〈111 pole, corresponding to the {111} plane along which preferred grain growth occurs. Although the rotation axes approach the normal vector of the preferred slip planes they only rarely coincide with the exact location of the 〈111〉 directions. For the particular case of grains elongated along the (111) and (11−1) planes, the rotation axes are situated near the [111] and [11−1] poles, respectively. Only a small number of grains are elongated along traces of two other {111} planes. In ND/ED section they run vertically, i.e. along ND direction (Fig. 14 a). None of the grains grows horizontally, i.e. parallel to TD. Image 1